Multi-layer security based multiple image encryption technique. (March 2023) - Sabir, Shazia; Guleria, Vandana
Abstract: This paper designs a novel multiple image encryption technique utilizing affine Hill cipher (AHC), reality-preserving two-dimensional discrete fractional Hartley transform (RP2DFrHT) and generalized two-dimensional (2D) Arnold map (AM). In our technique, three indexed images are obtained from three color images. Afterwards, AHC performs a strong degree of confusion and diffusion operations and RP2DFrHT provides real domain output image. Lastly, 2D AM dislocates the image pixel position. After the encryption process, single-channel real-valued encrypted image is obtained which gives convenience in the display, storage and transmission of an image over an unsecured network. The proposed technique is multi-layer secured in the time, frequency and co-ordinate domains. Moreover, the secret keys, arrangements and positions of used parameters all are imperative for the correct decryption process of our technique. Simulation results, security analysis, statistical analysis and comparison analysis ensure that the proposed technique has an excellent encryption effect, sufficient security and robustness. Graphical abstract: Highlights: This paper uses three fascinating algorithms to do multiple image encryption (MIE). The first level of encryption provides a strong degree of confusion and diffusion operations. The second level of encryption provides the real-valued output and improves the efficiency of MIE. The third level of encryption dislocates the pixel position and provides high level of randomness. The proposed MIE has an excellent encryption effect and sufficient security.